The properties of particles produced from waste plywood by shredding in a single-shaft shredder - Laskowska, Agnieszka; Mamiński, Mariusz (Maderas. Ciencia y Tecnología, 2020)
The present work regards an attempt to obtain particles from the post-industrial pine plywood in a single-shaft shredder. A screen mesh size determines the wood particles characteristics. In the work 10–, 14–, 25– and 38–mm mesh size screens were used. The urea-formaldehyde (UF) and phenol-formaldehyde (PF) bonded plywood were shredded separately, so that the effect of the binder type could be analyzed. The determined fractional composition, bulk density, dimensions and surface area of the particles were compared to the industrial virgin pine particles dedicated to the core layer of particleboards. The results showed that the particles obtained from a 14–mm mesh screen exhibited properties closest to those found for the virgin particles.